Neuro-Symbolic Enforcement Engines for Proactive Financial Crime Prevention - Mallikarjun Reddy Gouni (International Journal of Computational and Experimental Science and Engineering, 2026)
Financial organizations are faced with unprecedented challenges in identifying complex financial crimes that utilize AI, Deepfakes, and Multi-Level Obfuscations. Current compliance solutions are far from adequate by virtue of high levels of false positives and ineptness in spotting new forms of money crimes. Neuro-symbolic enforcement engines can be considered revolutionary solutions that seek to combine neural-based anomaly recognition and symbolic problem-solving capabilities for the proactive prevention of financial crimes. These novel solutions seek to combine transformer-based sequence models for temporal analysis of financial transactions with graph neural networks that represent regulatory policies as symbolic logic structures. These engines enable the system to recognize complex patterns in high-value financial transaction data as well as make rationalized decisions based on formalized compliance rules. Contrastive learning strategies can be used for improved identification of hidden criminal patterns in financial data by adequately addressing the high levels of class imbalance commonly found in Anti-Fraud analytics. Proactive predictive simulation for compliance outcomes on potentially criminal activity before escalation can be used for preemptive action plans. Generative models can be used for simulating new money crime scenarios for adversarial Validation. Real-time processing requirements for enforcement engines and satisfaction conditions for fairness on diverse customer sets can be considered as challenges for implementation.